2010
DOI: 10.1177/230949901001800316
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle-Spoke Injuries of the Foot in Children

Abstract: Bicycle-spoke injuries usually affected the ankle region, and the wound was usually deeper than it appeared on initial examination. Reassessment of the wound after 48 hours is recommended. Severity of soft-tissue injury was the determinant of overall function; bone fractures by themselves did not alter the duration of recovery. To prevent bicyclespoke injuries, spoke guards and foot rests should be used, and children being carried on a bicycle should wear proper shoes. Education on injury mechanism, severity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
1
18
0
1
Order By: Relevance
“…Severe injury to heel may lead to heel pad avulsion and often transaction of tendoachilles. 2,6 Results of our study were consistent with them. In literatures, it has been shown that bicycle spoke injuries have resulted in severe heel pad injury, transaction of tendo-achilles and warranted the need for flap surgeries to cover the wounds.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Severe injury to heel may lead to heel pad avulsion and often transaction of tendoachilles. 2,6 Results of our study were consistent with them. In literatures, it has been shown that bicycle spoke injuries have resulted in severe heel pad injury, transaction of tendo-achilles and warranted the need for flap surgeries to cover the wounds.…”
Section: Discussionsupporting
confidence: 90%
“…An ankle foot orthosis or a back splint is also recommended as it helps in good healing and exercise to be performed. 2 Various modifications in bicycle has been advised for preventing such injuries, like mesh cover, or plastic shield to bridge the gap between fork and horizontal upright of bicycle etc. 9 Making the people aware of the mode of injury and preventive measures explained at the costumer level of bicycle could decrease the incidence of these injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The spectrum of spoke wheel injury ranges from minor soft tissue laceration to extensive crush injury with tendon and bony involvement to subtotal amputations, mainly involving heel and ankle sites. [2][3][4] Management of the spoke wheel injuries is often challenging and is based on the location and grade of injury. Oestern and torcycle.…”
Section: Introductionmentioning
confidence: 99%
“…6 88 17 95 18 93 88 87 19 102 94 90 20 92 87 84 21 104 83 82 82 80 22 88 83 23 99 88 84 82 81 24 87 25 101 84 81 26 89 82 27 82 28 87 82 83 29 92 88 30 91 31 91 84 84 …”
Section: Monthunclassified